The Response of the German Agricultural Sector to the Envisaged Biofuel Targets in Germany and Abroad: A CGE Simulation - Sorda, Giovanni; Banse, Martin (German Journal of Agricultural Economics, 2011)
This article analyses the impact of national, European and global biofuel targets on German food production and land allocation until 2020. The LEITAP General Equilibrium Model simulates the interaction of agricultural and energy markets in response to the envisaged expansion of the biofuel industry. First generation biofuels are integrated in the production structure of the petroleum sector. Second generation biofuels are modelled indirectly via estimated bottom-up reductions in land available for agriculture. Biofuel targets are set exogenously according to the current policy goals. The model recursively responds to increments in the biofuel mandates over three time intervals. Each country or region is required the meet its respective target and is allowed to subsidize biofuel consumption through a budget-neutral mechanism. Thanks to a nested land specification, changes in land use take into account variable elasticities of substitution among different cultivations. The results indicate that German production of biofuel crops substantially increases. In particular, oilseed output experiences a remarkable growth. Land allocation and land prices also change significantly. However, higher production does not suffice to satisfy the demand for biofuels feedstock, and imports of oilseeds and sugar rise considerably. Moreover, the model suggests that the growth in biofuel crop production among the remaining EU-26 countries is driven by the new Member States of the EU, and that the supply of EU biofuel crops also has to be enhanced by imports from abroad. Biofuel policies outside Europe show only little additional impact on German agriculture. The projected changes in food commodity prices are in line with the results of other CGE analyses, although prices rise to a lesser extent than projected in studies based on Partial Equilibrium Models.